Eiropas Savienības tiesiskais regulējums tādu iepirkuma līgumu piešķiršanā, uz kuriem pilnībā vai daļēji neattiecas Publiskā iepirkuma direktīvās paredzētie noteikumi - Mežalis, Ēriks (Latvijas Universitāte, 2008)
The theme of bachelor paper – current legal problems in awarding public procurement contracts, being fully or partially excluded form ratione materiae of EU Public Procurement Directives – is related to actual practical concerns on effective functioning of Internal Market in field of public contracts. Above mentioned directives provide for procurement procedure only if the estimated value of public contract exceeds certain financial amount, and thus it is extremely important – which is also the aim of bachelor paper - to clarify the obligations of contracting authorities when awarding the contracts below these financial thresholds. No less important is to find out the scope of obligations of contracting authorities when awarding so-called non – priority contracts placed in Annex XVII B of Directive 2004/17/EC and Annex II B of Directive 2004/18/EC. Author is analyzing the connection between the European Primary and Secondary law on Public Procurement, using the rulings of ECJ, clarifications by European Commission, as well as opinio juris and opinion of legal authors. Author is examining the content of Fundamental Principles of EC Treaty and providing an in – depth analysis regarding the obligations of contracting authorities stemming from them. As the most significant problem in awarding public procurement contracts, being fully or partially excluded form ratione materiae of EU Public Procurement Directives, author recognizes the lack of legal certainty regarding the concrete obligations of contracting authorities in awarding process, and their scope Author therefore proposes solutions for mentioned problem, that can be also used as an output for discussion on some possible changes in EU Public Procurement Law.
Current legal problems in awarding public procurement contracts, being fully or partially excluded form ratione materiae of EU Public Procurement Directives
Keywords: Juridiskā zinātne